Identification of host genetic factors modulating β-lactam resistance in Escherichia coli harbouring plasmid-borne β-lactamase through transposon-sequencing - Kim, Hyunhee; Bell, Travis; Lee, Kihyun; Jeong, Jeongyun; Bardwell, James C.A.; Lee, Changhan (Emerging Microbes and Infections, 2025)
Since β-lactam antibiotics are widely used, emergence of bacteria with resistance to them poses a significant threat to society. In particular, acquisition of genes encoding β-lactamase, an enzyme that degrades β-lactam antibiotics, has been a major contributing factor in the emergence of bacteria that are resistant to β-lactam antibiotics. However, relatively few genetic targets for killing these resistant bacteria have been identified to date. Here, we used a systematic approach called transposon-sequencing (Tn-Seq), to screen the Escherichia coli genome for host genetic factors that, when mutated, affect resistance to ampicillin, one of the β-lactam antibiotics, in a strain carrying a plasmid that encodes β-lactamase. This approach enabled not just the isolation of genes previously known to affect β-lactam resistance, but the additional loci skp, gshA, phoPQ and ypfN. Individual mutations in these genes modestly but consistently affected antibiotic resistance. We have identified that these genes are not only implicated in β-lactam resistance by itself but also play a crucial role in conditions associated with the expression of β-lactamase. GshA and phoPQ appear to contribute to β-lactam resistance by regulating membrane integrity. Notably, the overexpression of the uncharacterized membrane-associated protein, ypfN, has been shown to significantly enhance β-lactam resistance. We applied the genes identified from the screening into Salmonella Typhimurium and Pseudomonas aeruginosa strains, both critical human pathogens with antibiotic resistance, and observed their significant impact on β-lactam resistance. Therefore, these genes can potentially be utilized as therapeutic targets to control the survival of β-lactamase-producing bacteria.
Keywords: Ampicillin; Anti-Bacterial Agents; beta-Lactam Resistance; beta-Lactamases; beta-Lactams; DNA Transposable Elements; Escherichia coli; Escherichia coli Proteins; Humans; Microbial Sensitivity Tests; Mutation; Plasmids; Escherichia coli; gshA; phoPQ; Pseudomonas aeruginosa; skp; ypfN; β-lactam resistance; β-lactamase producing bacteria